Simsia bicentenarialis (Compositae-Heliantheae) a new species of the central part of Mexico - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2010)
Simsia bicentenarialis from northeastern and central Queretaro and northeastern Guanajuato is described as new and illustrated. It shows similarities with some varieties of S. foetida (Cav.) S. F. Blake.